Pengaruh Penerapan Model Pembelajaran POGIL untuk Meningkatkan Pemahaman Peserta Didik pada Kelas XI SMKS Mahyal Ulum Al-Aziziyah - Abrar Syahrul Fajri; Hari Anna Lastya; Malahayati Malahayati (PTE FTK UIN Ar-Raniry, 2023)
The POGIL model is a student-centered learning model with a collaborative learning type using guided inquiry that improves students' understanding of the learning process. However, the research aims to see changes in student's conceptual understanding before and after the implementation of the POGIL model. The research methodology uses a quantitative approach with a quasi-experimental one-shot case study involving 14 students of SMKS Mahyal Ulum in the motorcycle ignition system material department with data collection carried out by tests (pre-test and post-test). The results showed that the average score for the pre-test was 42, 14 while the post-test results had an average score of 63, 57. It is proven that the POGIL learning model can increase students' understanding of learning by 33, 71%. The results of the hypothesis test using the t-test obtained a value of 0.024 > 0.05 so Ho is rejected and Ha is accepted. From the research, it could be concluded that the POGIL is believed to improve students' knowledge.